RA V5 N2, Message from the Editor in Chief (May - August 2015) - Castro Borges, Pedro (Revista ALCONPAT, 2015)
JOURNAL OF THE LATIN-AMERICAN ASSOCIATION OF QUALITY CONTROL, PATHOLOGY AND RECOVERY OF CONSTRUCTION. http://www.revistaalconpat.org It is a proud and joyful moment for the Revista ALCONPAT team to see the third and last issue of our fifth year published. The objective of the Revista ALCONPAT (RA) is the publication of case studies related to the topics of our association, quality control, pathology and construction recovery, motivating the presentation as well of basic or applied research that could be applied to case studies. In this V5N2, we start with our special guest article from Argentina. Edgardo F. Irassar and colleagues discuss the hydration and properties of ternary cements with calcareous filler and slag. Their results showed a limitation of the filler content to obtain an adequate response of the mechanical resistance and durable to long ages, and of the slag content to obtain appropriate values at an early age. In the second paper, C. G. N. Marcondes and his colleagues from Brazil discuss the influence of dispersion on the mechanical properties and water absorption of carbon nanotubes in Portland cement concrete. The ultrasonic technique was relevant to obtain the dispersion of the nanotubes and with it an improvement of the mechanical properties The third article D. MartÃnez-Vásquez and colleagues from Mexico study the potential of the method of synthesis of ceramic-cement materials processed by alternative routes. Among their results they report that the proposed processing was promising to obtain high mechanical properties in short curing times. Our fourth article comes from Brazil, where Denis Cley S. Amorim and Dênio Ramam C. Oliveira show a work of Structural Reinforcement of a Historic Building in the City of RÃo Blanco in Arce. It is to highlight and discuss the aspect of the encamisamiento of elements for the reinforcement The fifth work of this issue is written by Goncalo T. Ferraz, Jorge de Brito and his colleagues from Portugal, who work on integrated management systems in buildings. His model draws much attention where they consider various pathology tables for building management In the sixth article from Brazil, J. Ligia. V. Real and colleagues present the state of the art on the colorimetric method by pulverization of silver nitrate to evaluate the penetration of chlorides in concrete. Between their results they report the influence of the type of cement in the answer of the colorimetric method Each RA issue aims to balance the participation of topics concerning the social objectives of the International ALCONPAT. We are grateful for the authors’ collaboration on this issue, their resolve and effort to comply with the established quality and deadlines. Each issue of the magazine will include the articles in the original language, and before the following issue the versions in other languages will be published. The official languages of the Revista ALCONPAT are English, Spanish and Portuguese The Editorial Board Pedro Castro Borges Editor in Chief